The effect of surface treatment and environmental actions on the adhesive connection between GFRP laminate surface and fresh FRC. (20th October 2020) - Sena-Cruz, José; Correia, Luís; Ribeiro, Filipe; Figueira, Diogo; Benzo, Pier Giovanni; Barros, Joaquim; Pereira, Eduardo; Valente, Isabel
Graphical abstract: Highlights: Evaluation of the adhesive connection between GFRP plates and FRC. Use of fresh steel fiber reinforced self-compacting concrete. Effect of distinct commercially available adhesives and surface preparation methods. Effect of different environmental actions and exposure duration. Variance analysis (ANOVA) to determine the most relevant factors. Abstract: An experimental study on the performance of adhesive connection between Glass Fibre Reinforced Polymer (GFRP) plates and Steel Fibre reinforced self-compacting Concrete (FRC) was conducted. Fresh FRC was poured out onto the surface of GFPR plates, to create 40 square specimens (300 by 300 by 45 [mm]). Pull-off tests were performed to evaluate the tensile strength of the adhesive connection when different types of adhesives (four) and surface treatments (three) are used. Furthermore, the effect of five different environmental conditions on the tensile strength of the adhesive connection was also evaluated. After analysing the results and performing a variance analysis (ANOVA), it has been shown that the pull-off behaviour is highly influenced by the type of adhesive and by the environmental action. In spite of that, the dominant failure mode was cohesive failure in the FRC substrate, therefore good bond conditions between both materials were achieved.